Vibration Isolation Review: II. Shock Excitation - F.C. Nelson (Shock and Vibration)
This is the second part of a two part review of shock and vibration isolation. It covers three distinct categories of shock excitation—pulselike shock, velocity shock, and complex shock—and discusses the means that are available in each case to measure the effectiveness of shock mitigation by the imposition of flexible connections between the isolated system and its base.